Capacity for the management of kidney failure in the International Society of Nephrology Oceania and South East Asia (OSEA) region: report from the 2023 ISN Global Kidney Health Atlas (ISN-GKHA) - Francis, Anna; Wainstein, Marina; Irish, Georgina; Abdul Hafidz, Muhammad Iqbal; Chen, Titi; Cho, Yeoungjee; Htay, Htay; Kanjanabuch, Talerngsak; Lalji, Rowena; Neuen, Brendon L.; See, Emily; Shah, Anim; et al. (Elsevier, 2024)
The International Society of Nephrology (ISN) region of Oceania and South East Asia (OSEA) is a mix of high- and low-income countries, with diversity in population demographics and densities. Three iterations of the ISN Global Kidney Health Atlas (GKHA) have been conducted, aiming to deliver in-depth assessments of global kidney care across the spectrum from early detection of CKD to treatment of kidney failure. This paper reports the findings of the latest ISN-GKHA in relation to kidney-care capacity in the OSEA region. Among the 30 countries and territories in OSEA, 19 (63%) participated in the ISN-GKHA, representing over 97% of the region’s population. The overall prevalence of treated kidney failure in the OSEA region was 1203 per million population (pmp), 45% higher than the global median of 823 pmp. In contrast, kidney replacement therapy (KRT) in the OSEA region was less available than the global median (chronic hemodialysis, 89% OSEA region vs. 98% globally; peritoneal dialysis, 72% vs. 79%; kidney transplantation, 61% vs. 70%). Only 56% of countries could provide access to dialysis to at least half of people with incident kidney failure, lower than the global median of 74% of countries with available dialysis services. Inequalities in access to KRT were present across the OSEA region, with widespread availability and low out-of-pocket costs in high-income countries and limited availability, often coupled with large out-of-pocket costs, in middle and low-income countries. Workforce limitations were observed across the OSEA region, especially in lower middle–income countries. Extensive collaborative work within the OSEA region and globally will help close the noted gaps in kidney-care provision.